2016
DOI: 10.7717/peerj.1899
|View full text |Cite
|
Sign up to set email alerts
|

People with gambling disorder and risky alcohol habits benefit more from motivational interviewing than from cognitive behavioral group therapy

Abstract: Background. Effective psychological treatment, including cognitive behavioral therapy and motivational interviewing (MI), is available for people with problematic gambling behaviors. To advance the development of treatment for gambling disorder, it is critical to further investigate how comorbidity impacts different types of treatments. The purpose of this study was to investigate whether screening for risky alcohol habits can provide guidance on whether people with gambling disorder should be recommended cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…While other behavioral health programs have successfully utilized group-based approaches to address GD treatment (Carlbring et al, 2009;Jiménez-Murcia et al, 2007, few, if any, are guided by manuals tailored specifically for individuals with GD and other co-occurring disorders. Instead, most are guided by CBT (Josephson et al, 2016) or other similar therapeutic approaches (e.g., mindfulness-based cognitive therapy; de Lisle et al, 2011). Individual practitioners, then, select methods by which to apply these theories, often guided by theoretical models that apply CBT concepts to GD (see Sharpe & Tarrier, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While other behavioral health programs have successfully utilized group-based approaches to address GD treatment (Carlbring et al, 2009;Jiménez-Murcia et al, 2007, few, if any, are guided by manuals tailored specifically for individuals with GD and other co-occurring disorders. Instead, most are guided by CBT (Josephson et al, 2016) or other similar therapeutic approaches (e.g., mindfulness-based cognitive therapy; de Lisle et al, 2011). Individual practitioners, then, select methods by which to apply these theories, often guided by theoretical models that apply CBT concepts to GD (see Sharpe & Tarrier, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…These modules were developed specifically to address issues related to gamblers with cooccurring disorders. For example, in the "Rational Thinking" module, the counselor facilitated group-based MI sessions, an approach used more frequently to address behavioral and substance use disorders (see Krejci & Neugebauer, 2015;Velasquez et al, 2006) than GD (see Josephson et al, 2016). In this module, participants listed various life events that might trigger co-occurring disorders like depression, anxiety, substance abuse, and other potentially harmful behaviors, and the facilitator then discussed pathways by which these behaviors can, in turn, trigger unwanted gambling behaviors.…”
Section: Interventionmentioning
confidence: 99%
“…The intervention is carried out by Svenska Spel staff trained in MI. All staff involved have undergone at least a 3 days MI training by a licensed psychologist experienced in gambling-related research ( 28 ), and they regularly receive updated training, as well as individual and group supervision in MI.…”
Section: Methodsmentioning
confidence: 99%
“…All psychological interventions have globally been shown to be effective in reducing gambling symptoms compared with no treatment or waitlist control conditions [13,14]. With respect to the specific therapeutic methods, studies have shown that the best efficacy is achieved with a cognitivebehavioral approach [5,7,8,11,15,16], as well as with interventions using motivational interviewing techniques [15][16][17][18][19].…”
Section: Psychological Interventionsmentioning
confidence: 99%